Understanding and working with different worldviews to co-design cultural security in clinical mental health settings to engage with Aboriginal and Torres Strait Islander clients - Wright, Michael; Lin, Ashleigh; O'Connell, Margaret; Bullen, Jonathan; Flavell, Helen (Cambridge University Press, 2021)
Background: Creating the conditions for meaningful relationships is essential to understanding Aboriginal worldviews and co-designing ways of working to achieve better health outcomes. Non-Aboriginal health professionals struggle to recognise the importance of social relationships to Aboriginal peoples and tensions emerge due to these different worldviews informed by different ontologies and epistemologies. This is more so in clinical settings where training and models of care are often inadequate for working with Aboriginal people. The impact of different understandings of relationships on the provision of health services to Aboriginal peoples remains under-researched. There is a critical need to reassess the way clinicians are supported by their organisations to engage with Aboriginal clients in competent and meaningfully ways.